Conceptualizing an antiracist framework for neuroscience research in art therapy: a qualitative pilot study - Kruk-Borisov, Kerry A. (Frontiers in Human Neuroscience, 2025)
IntroductionAdvances in social cognitive neuroscience research have contributed deeper understanding of neural processes relevant to art therapy, and of social, interrelational phenomena including racism and implicit bias. Confoundingly, emerging critical discourse about neuroscience research design highlighted systemic racism, implicit bias, and inequality perpetuated by imaging technologies, lack of diversity, and funding disparities. Emphasis toward antiracist practices within cognitive neuroscience research and various other fields has grown; however, literature on antiracist research practices within art therapy research is scant.MethodsThe purpose of this qualitative pilot research study was to elicit conceptualizations about antiracist research practices from art therapy researchers in response to relevant literature. Purposive sampling was used to recruit four female art therapy researchers from the United States (U.S.) and Europe. Semi-structured interviews were analyzed using grounded theory coding resulting in three main categories, seven themes, and subthemes. Member-checking and reflexive journaling were employed to enhance credibility.ResultsCore categories revealed points of convergence across participants, areas of concern, and requirements outlining antiracist research practices in art therapy. The first core category, shared beliefs and values, had three themes: neuroscience-informed perspective of art therapy; neuroscience research can strengthen art therapy theories; and infusion of antiracism and neuroscience into art therapy begins with education. The second core category, barriers and challenges, had two themes: potential credibility and legitimacy concerns for art therapy; and difficult conversations about disparities in awareness, diversity, and resources. The third core category, requirements and responsibilities for antiracist research, had two themes: due diligence to build accountability and legitimacy; and inclusion of diversity in art therapy research, and subthemes.DiscussionPreliminary outcomes revealed ideas aligning current antiracist neuroscience research discourse with art therapy experimental research practices. The small group of neuroscience-focused art therapist researchers provided realistic considerations about amplifying discourse within the art therapy profession and infusing antiracist research into neuro-informed art therapy curriculum, and prioritizing diversity throughout experimental research design. An antiracist art therapy research framework with principles including education, intentionality, and diversity was proposed, along with recommendations for further research using the framework and to implement the framework into graduate art therapy education.